Fine-Tuning of Type I Interferon Response by STAT3 - Tsai, Ming-Hsun; Pai, Li-Mei; Lee, Chien-Kuo (Frontiers in Immunology, 2019)
Type I interferon (IFN-I) is induced during innate immune response and is required for initiating antiviral activity, growth inhibition and immunomodulation. STAT1, STAT2 and STAT3 are activated in response to IFN-I stimulation. STAT1, STAT2 and IRF9 form ISGF3 complex which transactivates downstream IFN-stimulated genes and mediates antiviral response. However, the role of STAT3 remains to be characterized. Here, we review the multiple actions of STAT3 on suppressing IFN-I responses, including blocking IFN-I signaling, downregulating the expression of ISGF3 components, and antagonizing the transcriptional activity of ISGF3. Finally, we discuss the evolution of the suppressive activity of STAT3 and the therapeutic potential of STAT3 inhibitors in host defense against viral infections and IFN-I-associated diseases.